Impact of entrepreneurial and management experience on early performance - Stuart, Robert W.; Abetti, Pier A. (Journal of Business Venturing, 1990)
Venture capitalists have traditionally heavily weighted the previous experience, especially entrepreneurial experience, of the lead entrepreneur in their evaluation of the attractiveness of new ventures. This study quantitatively measures the relative early performance impact of this experience factor as well as the impact of several other experience and firm characteristics. Measurements were obtained on the environment, strategy, type of organization, entrepreneur's personality and attitude, and various measurements on the experience of entrepreneur and the team. The data were obtained in personal interviews with the chief executives of 52 new technical ventures in the New York/New England area. The entrepreneurial experience, namely the number of previous new venture involvements and the level of the management role played in such ventures was by far the most significant factor. Other experience factors such as age, years of business, management, and technical experience, various dimensions of the entrepreneurial team's experience, etc., were not significantly related to performance. Interestingly, advanced education beyond the bachelor's degree did not help but was negatively related to performance. The best way to learn about making a company successful is to work in, or better to run a new firm. Time spent in new ventures is dramatically more valuable than time spent in school or large firms. Therefore venture capitalists are correct in emphasizing previous entrepreneurial experience in their evaluation. On the other hand, general business, management, or technical experience may be over-emphasized in a venture capitalist's evaluations. Also those considering an entrepreneurial career would be wise to seek involvement or employment in new or newly established firms. Although the average personality of the entrepreneurs was similar to that observed by other researchers, personality was not a factor in firm performance. Certain personality types might tend